Two-phase Flow Visualization Employing Gauss-Newton Method in Microchannel - Yonghong Liu; Mingyan Zu; Xiantao Wang; Je-Eun Choi (Universitas Ahmad Dahlan, 2013)
Flow behaviour monitoring on the micro-scale is very important in many industrial and biochemical process. Electrical resistance tomography (ERT), as an alternative technique to visualize multi-phase flows, has high temporal resolution for monitoring fast transient processes. However, the complexity of microchannel fabrication end up with the difficulty of electrical data sampling and the non-linearity and ill-posedness of the inverse problem often cause the poor spatial resolution of the reconstructed images. Inthis paper, Agilent based data acquisition hardware was set up for reliable data retrieval from a novel microchannel. Gauss-Newton method with adaptive threshold (GNAT) technique was presented to improve the spatial resolution of ERT images.Preliminary experimental results reveal that ERT system based on Agilent data acquisition unit and GNAT method can effectively visualize the solid-liquid two-phase flow in microchannel.